How to catch a viscount - Burrows, Annie (Burrows, Annie. Patterdale siblings, 2022)
Miss Betsy Fairfax must marry to save her family from financial ruin. Only, her mother's overzealous efforts to find kindhearted Betsy a suitable match have made her society's most undesirable debutante! She's ready to give up and become a paid companion, when she shares a spine-tingling kiss with James, a charming steward. Hardly the way to catch a viscount, unless he's not entirely whom he seems...